Polymerization kinetics and microstructure of waterborne acrylic/alkyd nanocomposites synthesized by miniemulsion - Goikoetxea, Monika (2009)
Waterborne acrylic-alkyd nanocomposites are expected to combine the positive properties of alkyd resins and acrylic polymers. In this work the kinetics of the miniemulsion polymerization used to synthesize these nanocomposites and the effect of the process variables on the polymer architecture and particle morphology was investigated. It was found that resin hydrophobicity and the type of initiator strongly affected the microstructure of these materials. The mechanisms responsible for these effects were discussed.